The role of histone marks in genome organization and histone cross-talk in Magnaporthe oryzae - Rowe, David (Kansas State University, 2023)
Magnaporthe oryzae is the filamentous fungus that causes rice blast disease. The organization of genes and genetic variation in plant pathogenic fungal genomes is an important area of research to better understand the evolution of pathogens and genetic diversity of fungal populations. The organization of fungal genomes has been described in different ways. Some descriptions separate the genome into gene-dense and gene-sparse regions that differ in the abundance of effector genes and DNA variation, called the two-speed genome. Other fungal genomes have variable regions without differences in gene density. As such, it is unclear what description of genome organization is most relevant to understanding pathogen biology and evolution. Additionally, it remains unknown what factors drive particular descriptions of genome organization. One hypothesis is that the epigenome dictates genome organization described through the lens of variability and evolution. Under this model, active and repressive epigenetic histone modifications contribute to genome organization of stable and variable genomic regions, respectively, that have different evolutionary trajectories. To test this hypothesis, we completed four high-quality genome assemblies and histone modification maps to enable high-resolution analysis of DNA variation and the epigenome present in multiple reference strains, against a population of rice-infecting M. oryzae strains. Overall, the genomes of all four strains showed similar patterns of organization, defined by their epigenetic states, the presence of genes versus transposable elements (TEs) and their type of DNA variation. We did not find evidence of the genomes being organized into gene-dense and gene-sparse regions. The results showed that the repressive histone marks, H3K27me3 and H3K9me3, were associated with higher single nucleotide polymorphism frequencies in genes, while H3K27ac, a mark of active transcription, is associated with higher insertion and deletion mutation frequencies. The results support the hypothesis that the tested epigenetic marks are associated with specific types of genome variation and contribute to the organization of the genome. In addition to the comparative genomics research, we used a direct genetic approach to examine histone cross-talk and its role in transcription and genome organization. These experiments focused on tri-methylation of H3 Lysine 36 (H3K36me3) and H3 Lysine 27 (H3K27me3). This is because previous research in the lab showed that disruption of Polycomb Repressive Complex (PRC2), the enzyme complex responsible for methylating H3K27, also impacted the enrichment of H3K36me3, a mark typically associated with actively transcribed genes. Two lysine methyltransferases, Su(var)3-9, Enhancer of zeste, Trithorax-2, SET2, and absent, small, or homeotic-1, ASH1, are responsible for H3K36me3 in filamentous fungi, and single and double deletion strains for the two enzymes, [delta]set2 and [delta]ash1, were constructed. Phenotypic analysis showed that both enzymes are required for normal growth, development and host infection, indicating the broad importance of H3K36me3 in M. oryzae. Results from histone chromatin immunoprecipitation sequencing (ChIP) showed that ASH1 and SET2 function in separate genomic regions, consistent with results from other Ascomycetes. In M. oryzae, ASH1-mediated H3K36me3 largely overlapped regions of PRC2-mediated H3K27me3, and interestingly, the [delta]ash1 strain lost H3K27me3 in 56.5% of regions co-marked by ASH1 and PRC2. The results indicate that ASH1-mediated H3K36me3, but not SET2, can co-locate and sometimes be required for H3K27me3 deposition. The mechanism of this interaction is not known. The proposed function of H3K36me3 is to repress DNA transcription, and this could explain why the one mark is found in disparate regions of the genome. We propose that SET2-mediated H3K36me3 in actively transcribed genes slows transcription to prevent erroneous transcripts whereas ASH1-mediated H3K36me3 that frequently co-occurs in H3K27me3 marked regions of the genome helps contribute to stronger repression of genes in heterochromatin.
Keywords: Genome organization; Epigenetics